The iron giant - Bird, Brad; Abbate, Allison; McAnuff, Des; Warner Bros. Pictures (California : Warner Bros. Pictures, 2004)
A young boy meets a 50 foot tall, steel-eating giant which he tries to keep secret from everyone, including a nosey government agent
Title from title screen
Based on the book The iron man, by Ted Hughes
Voices: Jennifer Aniston, Harry Connick, Jr., Vin Diesel, Christopher McDonald
DVD Format
Keywords: Science fiction films; Heroes -- Drama; Robots -- Drama